Prepare to flow : how sports imagery ability affects flow state in top tier Icelandic football - Hreggviður Hermannsson 2000- (2023)
Imagery has been identified as one of the key factors contributing to athletes experiencing flow state during training/competition, flow state being the optimal performance. The objective of this study was to explore the imagery ability of top tier football players in Iceland and its association with flow state. The results of the current study corresponds with previous studies and gives an option of implementing imagery as interventions for Icelandic athletes. A chosen sample of 84 participants (male = 58, female = 26) between the age of 18 and 37 representing teams from Besta deildin took part in the study. A self-report questionnaire including Dispositional Flow Scale – 2 (DFS-2) and Sports Imagery Ability Questionnaire (SIAQ) was used to assess the current states of imagery ability and flow states. Results indicated that there was a significant and positive correlation between sports imagery ability and experiencing flow. In addition, sports imagery ability explained for 34.2% variance in flow state experiences in Icelandic top tier football players. Keywords: flow state, sports imagery ability, football, Icelandic athletes Skynmyndir virðast spila lykilhlutverk í upplifun flæðis meðal íþróttafólks bæði á æfingum og í leikjum. Markmið þessarar rannsóknar var að athuga skynmyndagetu ásamt upplifun flæðis leikmanna í efstu deild karla og kvenna í knattspyrnu á Íslandi og skoða samband breytanna tveggja. Niðurstöður þessarar rannsóknar samsvarar fyrri rannsóknum og getur þar með opnað nýjan möguleika á innleiðingu skynmyndunarþjálfunar hjá íþróttafólki á Íslandi. Úrtakið samanstóð af 84 þátttakendum (58 körlum og 26 konum) úr Bestu deildinni (efsta deild á Íslandi) á aldrinum 18 til 37 ára. Sjálfsmatskvarði sem innihélt meðal annars Sports Imagery Ability Scale (SIAQ) og Dispositional Flow Scale – 2 (DFS-2) var notaður til þess að meta skynmyndagetu og ástand flæðis. Niðurstöður sýndu að það var marktækt og jákvætt samband á mili skynmyndunargetu og flæðis leikmanna. Auk þess sem skynmyndunargeta útskýrði ...